ISSUES OF IMPROVING THE INSTITUTION OF REVIEW OF CIVIL CASES UNDER THE SUPERVISORY PROCEDURE - Khakimov Bunyod Turanazarovich (Modern American Journals, 2026)
This article analyses the legal basis for the introduction of the institution of reviewing civil cases under the supervisory procedure. It also briefly outlines the theoretical and practical problems associated with this institution. Furthermore, specific proposals are put forward as possible solutions to the identified problems.
Keywords: Supervisory procedure, complaint, judicial act, intermediate-level courts, regional supervisory courts